Introducción a "El menor y su protección: una aproximación plural. - Mariscal de Gante Mirón, Margarita; Serrano Ruiz Calderón, Manuel; García Villaluenga, Leticia (Cuadernos de Trabajo Social, 1997)
Sin resumen